Perioperative immunotherapy for esophageal squamous cell carcinoma - Wei, Dan D.; Fang, Jin M.; Wang, Huan Z.; Chen, Jian; Kong, Shuai; Jiang, Yan-Yi; Jiang, Yuan (Frontiers in Immunology, 2024)
Esophageal squamous cell carcinoma (ESCC) is the main prevalent histological subtype and accounts for 85% of esophageal cancer cases worldwide.Traditional treatment for ESCC involves chemotherapy, radiotherapy, and surgery.However, the overall prognosis remains unfavourable. Recently, immune checkpoint blockade (ICB) therapy using anti-programmed cell death-1 (PD-1) / PD-1 ligand (PD-L1) antibodies have not only achieved remarkable benefits in the clinical management of ESCC but have also completely changed the treatment approach for this cancer. In just a few years, ICB therapy has rapidly advanced and been added to standard firstline treatment regimen in patients with ESCC. However, preoperative immunotherapy is yet to be approved. In this review, we summarize the ICB antibodies commonly used in clinical immunotherapy of ESCC, and discuss the advances of immunotherapy combined with chemotherapy and radiotherapy in the perioperative treatment of ESCC, aiming to provide reference for clinical management of ESCC patients across the whole course of treatment.